2021
DOI: 10.1007/s13555-021-00534-8
|View full text |Cite
|
Sign up to set email alerts
|

Itch and Sleep Improvements with Baricitinib in Patients with Atopic Dermatitis: A Post Hoc Analysis of 3 Phase 3 Studies

Abstract: Introduction Burdensome symptoms of atopic dermatitis include itch and sleep disturbance. This post hoc analysis reports the effect of baricitinib on itch and sleep disturbance during the first week of treatment in 3 phase 3 studies. Methods Patients were randomized 2:1:1:1 to once-daily placebo or baricitinib 1 mg, 2 mg, or 4 mg in the BREEZE-AD1 and -AD2 studies and 1:1:1 to once-daily placebo or baricitinib 2 mg or 4 mg in the BREEZE-AD7 study. Topical corticosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…However, the numbers of patients These data further support previous findings that baricitinib provides rapid and durable relief for patients with AD [6,15]. A recent report has also shown rapid improvements in itch severity and sleep disturbance after treatment with baricitinib [16]. Similar to the improvements in skin pain, a significant reduction in itch severity is observed on the first day after first dose administration (day 2), as well as improvements seen in patients' ability to fall asleep, waking due to itch, and ability to return to sleep after being woken by itch.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the numbers of patients These data further support previous findings that baricitinib provides rapid and durable relief for patients with AD [6,15]. A recent report has also shown rapid improvements in itch severity and sleep disturbance after treatment with baricitinib [16]. Similar to the improvements in skin pain, a significant reduction in itch severity is observed on the first day after first dose administration (day 2), as well as improvements seen in patients' ability to fall asleep, waking due to itch, and ability to return to sleep after being woken by itch.…”
Section: Discussionsupporting
confidence: 83%
“…The phase 3 randomized, controlled monotherapy studies of baricitinib, BREEZE-AD1 and BREEZE-AD2, and the combination study of baricitinib with TCS, BREEZE-AD7, have shown that baricitinib improved signs and symptoms of AD, and was well tolerated [6,15]. Baricitinib has been shown to have a rapid effect on patient-reported outcomes (PROs) such as itch and sleep [16]. This analysis shows that a rapid improvement can also be achieved in skin pain and associated QoL measures reported through patient diaries in the studies BREEZE-AD1, BREEZE-AD2, and BREEZE-AD7.…”
Section: Introductionmentioning
confidence: 99%
“…Baricitinib was recently approved in atopic dermatitis 9 and showed rapid effects on the highly bothersome symptoms of itch and sleep disturbance. 10 Its rapid antipruritic properties, as demonstrated in our case study, suggest additional use for refractory chronic pruritus.…”
Section: Discussionmentioning
confidence: 62%
“…In a post hoc analysis of data from the first week of therapy in BREEZE-AD1 and BREEZE-AD2, baricitinib 4 mg significantly (nominal p ≤ 0.01 vs placebo) improved itch and sleep disturbance as early as day 2 (i.e. one day after the first dose), with these improvements maintained to day 7 [ 25 ]. Baricitinib 2 mg was associated with nominally significant between-groups differences relative to placebo in the proportions of patients achieving a clinically relevant POEM response (Table 2 ) and a DLQI total score of 0 or 1 response (nominal p ≤ 0.05) at week 16 in BREEZE-AD1 and BREEZE-AD2 [ 16 , 24 ].…”
Section: Therapeutic Efficacy Of Baricitinibmentioning
confidence: 99%